Advanced grammar in use: A self-study reference and practice book for advanced learners of english. - Hewings, Martin
Tenses. The future. Modals. Have, do, make, etc. Passives. Questions. Verbs. Reporting Articles. Determiners and quantifiers. Pronous. Adjectives. Adverbs. Prepositions.